EXPLORATION OF POTENTIAL TREE SPECIES IN SUMBA ISLAND - Lestari, Eka; Amin, Yusup; Pramasari, Dwi Ajias; Dwianto, Wahyu (Teknologi Indonesia, 2018)
ABSTRACTSumba Island is a part of Wallace region which located in between Asia and Australia continents. Therefore it has a lot of endemic flora and fauna species. Laiwangi Wanggameti National Park (LWNP) is one of area in Sumba Islands which represented of this condition. The aim of this study is to determine the potential of tree species in Sumba Island based on strength class and commercial class. The wood samples were taken from 9 plots by wood increment borer at 1.3 meters height (breast height). The physical properties (specific gravity) were measured to determine the wood strength classes. The results found 35 species of potential tree species which can be classified into strength class II (13 species), III (19 species), IV (2 species), and V (1 species). Based on commercial classes, 63% of the tree species were classified into lesser known timbers. Furthermore, we think the potential tree from LWNP can be used for research purpose in forestry, especially in domestication study. Keywords: wood strength class, commercial class, bor riap, Laiwangi Wanggameti National Park, domestication ABSTRAKPulau Sumba merupakan bagian dari kawasan Wallacea yang berada di antara Benua Asia dan Australia. Oleh karena itu, pulau ini memiliki banyak flora dan fauna endemik. Taman Nasional Laiwangi Wanggameti (TNLW) adalah suatu wilayah di Pulau Sumba yang merepresentasikan kondisi secara umum di kawasan tersebut. Tujuan dari penelitian ini adalah untuk menentukan jenis kayu potensial di Pulau Sumba berdasarkan kelas kuat dan kelas komersial. Sampel kayu diambil dari 9 plot dengan menggunakan bor riap pada ketinggian 1,3 meter (setinggi dada). Sifat fisik (berat jenis) diukur untuk menentukan kelas kuat kayu. Hasil menunjukkan bahwa ditemukan 35 jenis kayu yang potensial yang dapat diklasifikasikan ke dalam kelas kuat II (13 jenis), III (19 jenis), IV (2 jenis), dan V (1 jenis). Berdasarkan kelas komersial, 63% jenis kayu yang didapatkan merupakan jenis kayu yang kurang dikenal. Oleh karena itu, jenis-jenis kayu yang potensial dari TNLW ini dapat digunakan untuk kepentingan penelitian di bidang kehutanan, lebih khususnya pada penelitian tentang proses domestikasi jenis-jenis tersebut. Kata Kunci: kelas kuat kayu, kelas komersial, increment borer, Taman Nasional Laiwangi Wanggameti, domestikasi